Diversification Conglomerate Strategy - Tamara Dwi Rahayu (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Conglomerate diversification is a strategy of business expansion into sectors not directly related to the core business to spread risk and improve financial stability. This research aims to examine the concept, benefits, challenges and implementation of this strategy in supporting corporate growth in the modern era. With a qualitative approach based on literature review and case study analysis, this research uses secondary data from scholarly journals, company reports, and real cases such as General Electric (GE). The results show that conglomerate diversification is effective in creating financial stability, opening up innovation opportunities, and reducing dependence on a single sector. However, this strategy presents challenges such as increased operational complexity, lack of synergy between business units, and the risk of losing focus on the core business. This research emphasizes the importance of careful planning, internal capability evaluation, and managerial innovation to overcome these challenges.